Anti-allergic effects of sesquiterpene lactones from Saussurea costus (Falc.) Lipsch. determined using in vivo and in vitro experiments. (1st March 2018) - Lee, Bo-Kyung; Park, Soo-Jin; Nam, So-Yeon; Kang, Saeromi; Hwang, Jin; Lee, Seung-Jin; Im, Dong-Soon
Abstract: Ethnopharmacological relevance: Saussurea costus (Falc.) Lipsch. root has been used in Asian traditional medicine for the treatment of asthma, rheumatism, and other conditions. S. costus extracts were shown to alleviate house dust mite-induced atopic-like dermatitis in Nc/Nga mice; besides, sesquiterpene lactones were isolated from S. costus extracts. Aims of the study: We aimed to investigate the effects of sesquiterpene lactones (alantolactone, costunolide, and dehydrocostuslactone) in allergic asthma using female Balb/c mice and rat RBL-2H3 mast cells. Materials and methods: Antigen-induced degranulation was assessed by measuring β-hexosaminidase activity in vitro . In addition, a murine ovalbumin-induced allergic asthma model was used to test the in vivo efficacy of sesquiterpene lactones. Results: Sesquiterpene lactones inhibited antigen-induced degranulation, wherein dehydrocostuslactone > costunolide > alantolactone in potency. Administration of sesquiterpene lactones decreased the number of immune cells, particularly eosinophils, and reduced the expression and secretion of Th2 cytokines (IL-4 and IL-13) in the bronchoalveolar lavage fluid and lung tissues of mice with ovalbumin-induced allergic asthma. Histological studies showed that sesquiterpene lactones reduced inflammation and mucin production in the lungs. Similar to the in vitro study, dehydrocostuslactone showed the highest potency, followed by costunolide and alantolactone. Conclusion: These findings provide evidence that sesquiterpene lactones might be potential anti-allergic therapeutics. Graphical abstract: